Nitric Oxide Modulates Postnatal Bone Marrow-Derived Mesenchymal Stem Cell Migration - Fuseler, John W.; Valarmathi, Mani T. (Frontiers in Cell and Developmental Biology, 2016)
Nitric oxide (NO) is a small free-radical gas molecule, which is highly diffusible and can activate a wide range of downstream effectors, with rapid and widespread cellular effects. NO is a versatile signaling mediator with a plethora of cellular functions. For example, NO has been shown to regulate actin, the microfilament, dependent cellular functions, and also acts as a putative stem cell differentiation-inducing agent. In this study, using a wound-healing model of cellular migration, we have explored the effect of exogenous NO on the kinetics of movement and morphological changes in postnatal bone marrow-derived mesenchymal stem cells (MSCs). Cellular migration kinetics and morphological changes of the migrating MSCs were measured in the presence of an NO donor (S-Nitroso-N-Acetyl-D, L-Penicillamine, SNAP), especially, to track the dynamics of single-cell responses. Two experimental conditions were assessed, in which SNAP (200 µM) was applied to the MSCs. In the first experimental group (SN-1), SNAP was applied immediately following wound formation, and migration kinetics was determined for 24 hours. In the second experimental group (SN-2), MSCs were pretreated for 7 days with SNAP prior to wound formation and the determination of migration kinetics. The generated displacement curves were further analyzed by non-linear regression analysis. The migration displacement of the controls and NO treated MSCs (SN-1 and SN-2) were best described by a two parameter exponential functions expressing difference constant coefficients. Additionally, changes in the fractal dimension (D) of migrating MSCs were correlated with their displacement kinetics for all the three groups. Overall, these data suggest that NO may evidently function as a stop migration signal by disordering the cytoskeletal elements required for cell movement and proliferation of MSCs.